Experimental study of the incipient motion threshold of coral sediment for oscillatory flow. (15th June 2023) - Bian, Cheng; Chen, Jie; Jiang, Changbo; Wu, Zhiyuan; Yao, Zhen; Liu, Jiaxiang
Abstract: In this study, the incipient motion thresholds of coral sediment with the action of oscillatory currents were experimentally recorded by conducting a total of 405 laboratory experiments, including an analysis of nine sieve median diameters, five water depths, and four wave periods. The coral sediment Shields parameters for oscillatory flow were compared to those for unidirectional flow and to those of shell Shields parameters for oscillatory flow. The results showed that there was an extensive scatter range in the Shields parameter for oscillatory flow of coral sediments. Additionally, the coral sediment Shields parameter for oscillatory flow was slightly different from that for unidirectional flow. The use of the Shields curve form to represent the coral sediment threshold for oscillatory flow was not appropriate. Using the critical near-bottom peak velocity to represent the incipient motion threshold of coral sediment for oscillatory flow was a better option. The use of experimental particle data analyses and the equation for the critical near-bottom peak velocity of quartz sand for oscillatory flow was modified to obtain a critical near-bottom peak velocity equation for coral sediment. This equation adds the influence of shape through the median Corey shape factor. Highlights: The critical Shields parameters of coral sands under oscillatory flow are discussed in detail and compared with those under unidirectional flow. The critical wave parameters for coral sands in the case of critical incipient motion are discussed. The critical near-bottom peak velocity was used to represent the critical threshold for coral sands and a non-linear fit was used to obtain an equation to calculate the critical near-bottom peak velocity of coral sands. This equation adds the influence of shape through the median Corey shape factor.